Edibility of cultivated green seaweed Ulva intestinalis from Monkhali Beach, Cox’s Bazar coast of Bangladesh: bio-toxicity and heavy metal contents - Md. Mohibbullah; Md. Afzal Hossain; Mahfuzul Alam Mithu; Md. Maynul Islam; Mohammed Shariful Azam; Mohammed Nurul Absar Khan; Jae-Suk Choi (Scientific Reports)
Abstract Ulva intestinalis (UI) is widely available edible seaweed and has potential to be introduced as functional food items in Bangladesh. However, potential health hazards of this seaweed with biotoxicity assays and its relation to heavy metal contents were not evaluated previously. With these objectives, toxic effects of UI collected from floating raft culture in Monkhali Beach was evaluated using various organisms such as Chlorella vulgaris, Artemia salina, Daphnia magna, and Lactuca sativa. In relation to this effects, heavy metal concentrations (Fe, Cr, Ni, Cu, Zn, Pb, Cd, and As) and its potential health hazards were subsequently analyzed. The results showed that UI water extract had positive effects on the survivability and growth of the all-test organisms over different time periods, with minimal LC50 values, indicating no toxic to tested organisms. However, increased levels of total dissolved solids and electrical conductivity were observed as extract concentrations increased but considered to be safe below 5 mg kg−1, as compared to control. Moreover, Fe, Cr, Ni, Cu and Zn (43.60, 0.10, 0.44, 0.07, 0.27 and 0.13 mg kg−1 of dry weight, respectively) in UI were found to be low levels compared to previous studies, in addition, Cd and As remained not detected. No significant health risk (HQ < 1) and target carcinogenic risk were found. Therefore, UI could be utilized as functional foods or nutraceuticals for health-conscious consumers of Bangladesh without having potential risks.